Two New Species of the Genus Biston (Lepidoptera, Geometridae, Ennominae) from Central Asia - Viidalepp, J.R. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Описан Biston pljushtschi sp. n. из Гиссарского хребта, Таджикистан; вид относительно изолирован в группе видов B. stratarius (Hufnagel, 1767) рода Biston Leach, 1815. Biston stuningi Viidalepp sp. n. из Западного Памира и Западного Тянь-Шаня в Таджикистане, Узбекистане и Кыргызстане относится к группе B. betularius (Linnaeus, 1758), отличаясь рисунком крыльев, строением гениталий самца и задних ног. Проведено сравнение с типами Biston huberaria (Ballion, 1866) и B. tienschana Wehrli, 1940. Голотипы обоих новых видов хранятся в коллекции Института зоологии и ботаники (Тарту, Эстония), паратипы — в различных коллекциях. Biston pljushtschi Viidalepp sp. n. from the Hissar Mountain Range (Tadjikistan) is described. The species is relatively isolated in the B. stratarius (Hufnagel, 1767) group of species of the genus Biston Leach, 1815. Biston stuningi Viidalepp sp. n. from the West Pamirs and Western Tian-Shan in Tadjikistan, Uzbekistan and Kyrghyzstan belongs to the B. betularius (Linnaeus, 1758) species group of the genus, differing in its wing pattern, male genitalia and hindlegs armature. Types of Biston huberaria (Ballion, 1866) and B. tienschana Wehrli, 1940 are compared. Holotypes of the both new species are deposited in the collection of the Institute of Zoology and Botany (Tartu) (ZBI), paratypes in various collections.